The Oxford Handbook of Animal Organization Studies 2022
DOI: 10.1093/oxfordhb/9780192848185.013.20
|View full text |Cite
|
Sign up to set email alerts
|

Stockfree’s Short Shadow

Abstract: Academic, policy, and public debates have increasingly led to calls for the adoption of plant rich diets. Livestock’s ‘long shadow’—its high environmental footprint—and the need to transform food systems towards sustainable practices are widely recognized. However, despite their incremental normalization, vegan and vegetarian diets can still lead to fierce debates between people with different dietary identities. Arguing that identity-based understandings of who or what is ‘vegan’ obfuscate necessary changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Forms of animal-based agriculture are centered in sustainable agriculture discourse and practice. Meanwhile, approaches to sustainable agriculture that are exclusive of farmed animals sit at the margins of conversations about sustainable agriculture futuresdespite their actual and potential roles in sustainable agrifood systems (Hagemann and Potthast, 2015;Hirth, 2022). Nobari (2021) recently observed that "From First-World urban gardening enthusiasts to indigenous movements, the push for a more sustainable way of growing food-one that works with ecosystems instead of against them-comes from a diverse set of voices.…”
Section: Seymourmentioning
confidence: 99%
See 1 more Smart Citation
“…Forms of animal-based agriculture are centered in sustainable agriculture discourse and practice. Meanwhile, approaches to sustainable agriculture that are exclusive of farmed animals sit at the margins of conversations about sustainable agriculture futuresdespite their actual and potential roles in sustainable agrifood systems (Hagemann and Potthast, 2015;Hirth, 2022). Nobari (2021) recently observed that "From First-World urban gardening enthusiasts to indigenous movements, the push for a more sustainable way of growing food-one that works with ecosystems instead of against them-comes from a diverse set of voices.…”
Section: Seymourmentioning
confidence: 99%
“…AFOA approaches allow growers to avoid reliance on products from livestock industries or operations that they find environmentally irresponsible or morally reprehensible. 3 AFOA, including and beyond the three codified approaches introduced above, is a viable (e.g., Pimentel et al, 2005;Cormack, 2006;Eisenbach et al, 2019;Kakabouki et al, 2021;Kanisziewski et al, 2021;Hefner et al, 2022;Niether et al, 2023), less resource-intensive (Hirth, 2022) path forward in the face of numerous changes that may make animal-based plant agriculture and animal agriculture more tenuous or less enticing enterprises. The AFOA standards provide sets of agricultural principles and practices that sidestep these issues, particularly including methods for building soil fertility that do not rely on animal inputs.…”
Section: Afoa As An Asset To the Broader Sustainable Agriculture Move...mentioning
confidence: 99%